2011
DOI: 10.1145/2082156.2082163
|View full text |Cite
|
Sign up to set email alerts
|

GPU implementation and optimization of electromagnetic simulation using the FDTD method for antenna designing

Abstract: This paper describes electromagnetical field simulation using the 3D-FDTD method for antenna designing on a CUDAcompatible GPU. We use the Split Perfectly Matched Layer as an absorbing boundary condition. As is well known, the 3D-FDTD method is a kind of stencil computation and is considered better at GPU implementation. In order to find the best blocking size for the target GPU architecture, we empirically explore a design space of blocking size. We also propose a kernel fusing method as one of the efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Many work including ours have reported the block size has a strong effect on the performance [7]. Although the best size may depend on the presence or absence of each optimization technique, we used the block size of (B x , B y , B z ) = (32, 4, 32) based our primary evaluation results.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many work including ours have reported the block size has a strong effect on the performance [7]. Although the best size may depend on the presence or absence of each optimization technique, we used the block size of (B x , B y , B z ) = (32, 4, 32) based our primary evaluation results.…”
Section: Modelingmentioning
confidence: 99%
“…The FDTD method is known as a kind of stencil computation that has a high degree of parallelism but requires a large memory bandwidth. While GPU implementation is attractive as a cost-effective acceleration approach, our earlier work has shown that GPU implementation of Absorbing Boundary Conditions (ABCs) tends to be a bottleneck of the simulation [7]. We discuss this issue in this paper.…”
Section: Introductionmentioning
confidence: 99%